1999
DOI: 10.1107/s0108767399005401
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of crystal structural parameters using two-dimensional energy-filtered CBED patterns

Abstract: A new method to refine crystal structural parameters using convergent-beam electron diffraction (CBED), which is applicable to nanometre-size crystal structure analysis, is proposed. This method is based on the fitting between theoretical calculations and experimental intensities of energy-filtered two-dimensional CBED patterns containing higher-order Laue-zone (HOLZ) reflections. The use of HOLZ reflections is essential for the method because small displacements of atoms can be sensitively detected using HOLZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 26 publications
(11 reference statements)
0
93
0
Order By: Relevance
“…Dynamic simulation of the CBED patterns was performed using the Bloch-wave program ( Fig. 2 A2 and D2) (15). Agreement of the experimental patterns with the simulated ones confirmed that the sharp ZnO tips grow along the positive [0001] direction (i.e., Zn-polar direction), whereas the smooth tips grow along the negative ½0001 direction (i.e., O-polar direction).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Dynamic simulation of the CBED patterns was performed using the Bloch-wave program ( Fig. 2 A2 and D2) (15). Agreement of the experimental patterns with the simulated ones confirmed that the sharp ZnO tips grow along the positive [0001] direction (i.e., Zn-polar direction), whereas the smooth tips grow along the negative ½0001 direction (i.e., O-polar direction).…”
Section: Resultsmentioning
confidence: 82%
“…Simulated CBED patterns were obtained by many-beam dynamical calculations. The intensity calculation is based on the Bloch-wave formulation of dynamical theory (15). After the structural and chemical examinations, spatially resolved CL measurements on individual ZnO assemblies were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Spiral distortion is related to the rotation of the image that takes place in the magnetic electron lenses. Modern designs of magnetic electron lenses allow spiral distortion to be almost completely removed [18,19], or at least maintained below 1% if one has to work with beams subtending very large diffracting angles [20]. Our experience in dealing with HR imaging and SA diffraction reveals that the most relevant image affecting distortion can be approximated to be elliptical (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…124 of the 129 unique atoms (1176 in the unit cell) were found in the remarkably clean calculated potential maps ( Fig. 1) [2]. This investigation demonstrates that inorganic crystals of any complexity can be solved by electron crystallography.…”
mentioning
confidence: 70%
“…Distortion and background corrections were applied. A maximum of 91 reflections per pattern was fitted using the software package MBFIT, which provides a multi beam nonlinear least squares algorithm for zeroth order and higher order Laue zone (ZOLZ, HOLZ) reflections, fully based on dynamical diffraction theory [2]. The set of fitting parameters contains full structural information (atomic positions, anisotropic Debye-Waller-factors and low order structure factors).…”
mentioning
confidence: 99%